The determinants of behavioural intention to adopt e-wallet among the youth in UTAR - Cha, Pei Shan; Cheng, Jia Zhi; Cheu, Zhen Yar; Fan, Mun Keen (2021)
Malaysia is moving into a cashless society to replace cash with E-wallet applications. But many people continue to use money instead of using E-wallet applications. As a result, many researchers concern about the behavioural intention to adopt E-wallet among university students in developed countries. However, the students who studied in a private university in Malaysia, on the other hand, are often neglected, despite the fact that they are the primary potential users for the E-wallet applications in these countries. Hence, the study is carried out to examine the determinants of behavioural intention to adopt E-wallet among the youth in UTAR by including independent variables of perceived usefulness, consumer confidence, price value, facilitating condition and social influence by the aid of Unified Theory of Acceptance and Use of Technology (UTAUT) theory. There are 484 respondents are collected from UTAR Kampar and UTAR Sungai Long and the quota sampling technique is employed. Besides, the Statistical Package for the Social Sciences (SPSS) version 26.0 is used to conduct Multiple Linear Regression Analysis. The results concluded that perceived usefulness, consumer confidence and social influence have a significant relationship towards the behavioural intention to adopt E-wallet. Conversely, price value and facilitating condition have an insignificant relationship towards the behavioural intention to adopt E-wallet. Hence, universities and government agencies should concentrate to improve the behavioural intention to adopt E-wallet in Malaysia.